Pengaruh Konsentrasi Tragakan terhadap Mutu Fisik Sediaan Pasta Gigi Ekstrak Etanolik Daun Mahkota Dewa (Phaleria papuana Warb var. Wichnannii) sebagai Antibakteri Streptococcus mutans - Ika Andriana; Mimiek Murrukmihardi; Dewi Ekowati (Fakultas Farmasi Universitas Setia Budi, 2011)
Mahkota dewa leaf formulated in toothpaste preparation for easy it use. The physical properties of toothpaste preparations are influenced by the binder that tragacant. This study aims to determine the influence of tragacant concentration on the physical quality toothpaste Mahkota dewa leaf extract and antibacterial activity against Streptococcus mutans. This research is done with three toothpaste formula Mahkota dewa leaf maceration extract 70% ethanol with different concentrations of tragacant, these are 0,5% tragacant (FI), 1,0% tragacant (FII), and 1,5% tragacant (FIII). Toothpaste of Mahkota dewa leaf extract on the physical quality test (homogeneity, viscosity, dispersive power, and checks the degree of acidity) and test the antibacterial activity against Streptococcus mutans. Viscosity and dispersive power data were analyzed with two way anova. Data Minimum Inhibitory Concentration (MIC) and Minimum Bactericid Concentration (MBC) were analyzed by Kruskal Wallis test followed by Mann-Whitney analysis. The results showed that the MIC toothpaste Mahkota dewa leaf extract against Streptococcus mutans at a concentration of 18,75% and the MBC at a concentration of 37,5%. Tragacant binder concentration difference in each formula has effect on antibacterial activity but affects the viscosity and dispersive power supply.